Differential Rotational Movement of the Thoracolumbosacral Spine in High-Level Dressage Horses Ridden in a Straight Line, in Sitting Trot and Seated Canter Compared to In-Hand Trot - MacKechnie-Guire, Russell (Animals (Basel), 2021)
SIMPLE SUMMARY: As part of the investigative process of “loss of athletic performance”, quantitative data may help veterinary decision making when assessing equine back dysfunction. Ranges of motion of differential rotational movement were quantified between adjacent inertial measurement units, which were attached to the skin over the thoraco–lumbo–sacral area in 10 dressage horses. Differential rotational movements were collected during trot in-hand and ridden in sitting trot/canter during straight-line locomotion. For the thoracic area, differential heading values were smaller in sitting trot and canter compared to trotting in-hand. Compared to trotting in-hand the thoraco-lumbar differential pitch values were higher in sitting trot and canter. The lumbo-sacral region, differential pitch values were increased in canter compared to trotting in-hand and differential heading values were higher in sitting trot compared to canter. Compared to in-hand, reduced heading values were measured in the cranial–thoracic area and increased in the caudal–thoracic and lumbar area. Pitch values increased with ridden exercise from the caudal–thoracic to the sacral area. Back movement alters when ridden compared to an unloaded condition. Understanding back movement whilst being ridden will help advance our understanding on equine back movement and assist with decision making. ABSTRACT: Assessing back dysfunction is a key part of the investigative process of “loss of athletic performance” in the horse and quantitative data may help veterinary decision making. Ranges of motion of differential translational and rotational movement between adjacent inertial measurement units attached to the skin over thoracic vertebrae 5, 13 and 18 (T5, T13, T18) lumbar vertebra 3 (L3) and tuber sacrale (TS) were measured in 10 dressage horses during trot in-hand and ridden in sitting trot/canter. Straight-line motion cycles were analysed using a general linear model (random factor: horse; fixed factor: exercise condition; Bonferroni post hoc correction: p < 0.05). At T5-T13 the differential heading was smaller in sitting trot (p ≤ 0.0001, 5.1° (0.2)) and canter (p ≤ 0.0001, 3.2° (0.2)) compared to trotting in-hand (7.4° (0.4)). Compared to trotting in-hand (3.4° (0.4)) at T18-L3 differential pitch was higher in sitting trot (p ≤ 0.0001, 7.5° (0.3)) and canter (p ≤ 0.0001, 6.3° (0.3)). At L3-TS, differential pitch was increased in canter (6.5° (0.5)) compared to trotting in-hand (p = 0.006, 4.9° (0.6)) and differential heading was higher in sitting trot (4° (0.2)) compared to canter (p = 0.02, 2.9° (0.3)). Compared to in-hand, reduced heading was measured in the cranial–thoracic area and increased in the caudal–thoracic and lumbar area. Pitch increased with ridden exercise from the caudal–thoracic to the sacral area.